Dwie wizje tożsamości. Szkic z ontologii społecznej - Rogacz, Dawid (My University, 2013)
Arrangements in the field of ontology retain their importance for normative of political theory. The key problem of the ontology of social beings is human identity. This problem was raised during the debate between liberals and communitarians. Liberalism advocates the negative and formal concept of originality, evoked in modernist traditions. Communitarianism opts for the notion of identity with the values acclaimed in an individual community, which was established in the republican tradition. The final question is whether the differences between the heretics and the conventionalists are as significant as it is usually delineated.
Keywords: tożsamość; liberalizm; komunitaryzm